Molecular characterization of the incitant of cowpea bacterial blight and pustule, Xanthomonas campestris pv. vignicola - Verdier, Valerie M.; Assigbétsé, K.; Khatri-Chhetri, G.; Wydra, K.; Ruldoph, K; Geiger, JP (Springer, 1998)
Strains of Xanthomonas campestris pv. vignicola (Xcv), isolated from cowpea leaves with blight or minute pustules and collected from various geographic areas, were selected on the basis of pathological and physiological features. All strains were analyzed for genotypic markers by two methods: ribotyping with EcoRI endonuclease, and RFLP analysis with a plasmid probe (pthB) containing a gene required for pathogenicity from Xanthomonas campestris pv. manihotis. Ribotyping revealed a unique pattern for all the strains that corresponded to the previously described ribotype rRNA7. Based on polymorphism detected by pthB among Xcv strains, nine haplotypes were defined. The observed genetic variation was independent of the geographic origin of the strains and of pathogenic variation. Some haplotypes were widely distributed, whereas others were localized. In some cases, we could differentiate strains isolated from blight symptoms and pustules according to haplotypic composition. However, in most cases, no significant differences were observed. Our results and the previous pathogenic and biochemical characterizations suggest that the strains isolated from leaves with blight symptoms or minute pustules belong to the same pathovar. We provide information on pathogen diversity that can be used to identify and characterize resistant germplasm.